2021
DOI: 10.3390/plants10061231
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Botanical Product, Resveratrol, Effectively Suppresses Vesicular Stomatitis Virus Infection In Vitro

Abstract: Numerous natural phytochemicals such as resveratrol are acknowledged as potent botanical agents in regulating immune responses. However, it is less understood whether such immunomodulatory phytochemicals are appropriate for use as direct treatments in veterinary viral diseases. In the present study, we investigated the efficacy of resveratrol in suppressing vesicular stomatitis virus (VSV) infection. Outbreaks of VSV can cause massive economic loss in poultry and livestock husbandry farming, and VSV treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Based on the information contained in Table 2, it can be concluded that the mechanism of inhibition for individual polyphenols depends on the type of virus and its structure. Papers regarding the use of resveratrol [42,52,99] indicate the different mechanisms behind the inhibition of the viruses. It has been shown that it affects mainly the virus' replication cycle by interacting with the active sites of caspase or protein synthesis.…”
Section: Mechanism Of Antiviral Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the information contained in Table 2, it can be concluded that the mechanism of inhibition for individual polyphenols depends on the type of virus and its structure. Papers regarding the use of resveratrol [42,52,99] indicate the different mechanisms behind the inhibition of the viruses. It has been shown that it affects mainly the virus' replication cycle by interacting with the active sites of caspase or protein synthesis.…”
Section: Mechanism Of Antiviral Activitymentioning
confidence: 99%
“…quercetin SARS-CoV-2 interaction with Spike occurs between amino acid Thr 445, Ile 446; as for main protease it binds to Thr 26 superior main protease docking result compared to spike docking, better inhibitory effect on replication cycle of the virus rather than penetration/adsorption cycle [16] resveratrol Epstein-Barr virus decreasing levels of reactive oxygen species, blocking protein synthesis and inhibiting virus-induced activation of transcription factors, which affects replication of the individual virus [42] rotavirus inhibition of the replication in the Caco-2 cell line [52] vesicular stomatitis virus suppression of the spread of the virus by interaction with the active sites of caspase-3 and -7 [99] curcumin SARS-CoV-2 entry into host cells is also blocked by blocking the enzyme ACE2; curcumin has a high affinity for ACE2 ligands [60] influenza virus reduction of viral NA activity and blocking HA activity [69] SARS-CoV-2 inhibition due to interaction with Mpro receptor of SARS-CoV-2, which occurs by binding with amino acid Thr26, His41, Gln189…”
Section: Polyphenolmentioning
confidence: 99%